Food Inflation and Passenger Vehicle Purchases in South Africa: Cointegration, Short Run Dynamics and Causality - Tshiakambila, Eric Kateta; Chisasa, Joseph (Journal of Economics and Behavioral Studies, 2017)
Food inflation in South Africa has been observed to be a major source of underlying inflationary pressures in the economy due to its persistence beyond that of other commodities. In this regard, this study investigated whether an increase in the prices of food products has a significant effect on passenger vehicle purchases in South Africa. The Phillip-Perron (PP) test, showed vehicle purchases to be stationary in level while food inflation was stationary in the first difference. Using secondary time series data, the Johansen cointegration test revealed that the variables in the vehicle purchase function were cointegrated in the long run. The vector error correction model showed a long-run relationship, albeit insignificant, between food inflation and vehicle purchases. There was no evidence of a short run relationship between the two variables. The Granger causality test revealed no causal effect between the variables, regardless of the direction of the test. The study concluded that an increase in the prices of food products will not play a considerable role in consumers’ vehicle purchase decisions in South Africa. These results have policy implications for the motor and related industries.